Strategies to increase effective usage of MCH services in tribal areas of India – perspectives of health care personnel - Simarjeet Kaur (Journal of Family Medicine and Primary Care)
Introduction: Primary health care is essential for addressing the majority of a person’s health needs aligning with the ultimate goal of universal health coverage. Maternal and Child Health (MCH) Services are crucial for promoting the health and wellbeing of mothers and children. Healthcare personnel play a vital role in implementing MCH services, and they have proposed various strategies to enhance the effective delivery of healthcare services in tribal areas. Methodology: A qualitative study was conducted among 45 Health Care Personnel selected through the total enumeration sampling technique working in selected tribal areas of district Sirmaur, Himachal Pradesh. Semistructured in-depth interview was used to gather the data. Colazzi’s procedural steps were used to analyze the qualitative data of participants. Results: Findings revealed various strategies such as availability of sufficient resources and transportation, adequate working facilities, in-service education program, maintenance of records and reports, and beneficiaries involvement. Hence, all these strategies will overcome the challenges and facilitate the effective delivery of health care services in tribal areas.